2018
DOI: 10.1002/fsn3.651
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological assessment of maize ogi cofermented with pigeon pea

Abstract: Maize was cofermented with pigeon pea for ogi production and evaluated for microbiological qualities. White maize and pigeon pea were mixed at ratios of 90:10, 80:20, 70:30, 60:40, and 50:50, respectively, with 100:0 serving as the control. Mixtures were cofermented for 96 h at 27 ± 2°C, and microbiological and sensory qualities analyzed were carried out using analysis of variance. Values were significant at p ≤ .05. Results showed that there was a gradual decrease in the pH and increase in total titratable ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…It was observed that the pH levels of the processed samples shows loss in acidity compared to the unprocessed samples with agidi being the least acidic while the unprocessed maize samples was the most acidic. Omemu et al 23 reported similar pH levels between 4.07-6.07 in maize in their styles of the microbiological assessment of maize co-fermented with pigeon pea as obtained from this study.…”
Section: Resultssupporting
confidence: 74%
“…It was observed that the pH levels of the processed samples shows loss in acidity compared to the unprocessed samples with agidi being the least acidic while the unprocessed maize samples was the most acidic. Omemu et al 23 reported similar pH levels between 4.07-6.07 in maize in their styles of the microbiological assessment of maize co-fermented with pigeon pea as obtained from this study.…”
Section: Resultssupporting
confidence: 74%
“…A very strong negative correlation between pH and TTA was established ( r = −0.9511). Omemu, Okafor, Obadina, Bankole, and Adeyeye (2018) found the same relation between the above‐mentioned parameters during fermentation of maize: pigeon pea blends. Results of the ANOVA test indicated that there is a significant effect ( p < .05) due to the salt concentration (3.6 or 1.0 g/100 g), fermentation method (SMF or SSF) ( p < .05), and the interaction of these factors on the pH and TTA of Ps samples (on pH p < .05, on TTA p < .05).…”
Section: Resultsmentioning
confidence: 60%
“…The authors reported that the pH of maize dropped approximately from 6.6 to 4.3 during a 2-day fermentation, with higher fall being recorded in the last day. Slightly lower values (5.84-3.74) were however reported by Omemu, Okafor, Obadina, Bankole, and Adeyeye (2018).…”
Section: Changes In Some Selected Physicochemical Properties During Fmentioning
confidence: 65%